VARIASI KOMPOSISI SAMPAH BERBASIS SOSIO EKONOMI PEMUKIM PADA KOMPLEKS PERUMAHAN DI KELURAHAN BANYUNING - Putu Indra Christiawan (Media Komunikasi Geografi, 2017)
The accelerated of increase in the number of urban migrants adjoining the construction of unplanned housing. The construction of unplanned housing will produce pressure on the environment, especially the pressure of waste that is the outcome of the activity of the resident consumption. The aim of this study was to analyze the influence of resident characteristics with the waste composition in public housing in Banyuning Sub-district. The research method used is analytic survey. The analysis used in this research is descriptive statistics and inferential statistics. The results showed that the number of family members, education level and income level partially and simultaneously had a significant effect on the waste composition, both organic and non-organic waste in public housing in Banyuning Sub-district. This study concludes that it is necessary to design a form of waste management that is more specialized in urban waste generated by residential.